2017
DOI: 10.3390/s17040891
|View full text |Cite
|
Sign up to set email alerts
|

Fast Bragg Grating Inscription in PMMA Polymer Optical Fibres: Impact of Thermal Pre-Treatment of Preforms

Abstract: In this work, fibre Bragg gratings (FBGs) were inscribed in two different undoped poly- (methyl methacrylate) (PMMA) polymer optical fibres (POFs) using different types of UV lasers and their inscription times, temperature and strain sensitivities are investigated. The POF Bragg gratings (POFBGs) were inscribed using two UV lasers: a continuous UV HeCd @325 nm laser and a pulsed UV KrF @248 nm laser. Two PMMA POFs are used in which the primary and secondary preforms (during the two-step drawing process) have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…Nevertheless, the time taken for a POFBG inscription can be reduced by several orders of magnitude with the application of a 248 nm laser with low fluence and repetition rate through the phase mask technique [35]. It was also demonstrated that the inscription time can be lowered by performing a thermal treatment on the fiber preforms [33].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, the time taken for a POFBG inscription can be reduced by several orders of magnitude with the application of a 248 nm laser with low fluence and repetition rate through the phase mask technique [35]. It was also demonstrated that the inscription time can be lowered by performing a thermal treatment on the fiber preforms [33].…”
Section: Introductionmentioning
confidence: 98%
“…Such treatment provides a reduction of the internal stress in the fiber created during fabrication process. For this reason, it reduces the POFBGs sensors hysteresis, and can also decrease the inscription time and increase the grating stability [33]. The annealing can be made before the grating inscription (preannealing) or after the inscription (post-annealing).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can enhance the sensor strain sensitivity [39]. If the annealing is made on the fiber preform, it can increase the grating stability and reduce its inscription time [41], whereas, if it is made after the grating inscription, it can result in large blue-shift of the Bragg wavelength, especially when it is made under high humidity conditions [7]. Aiming at these advantages, the annealing was made in all POF samples employed.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, their strain performance can be enhanced through annealing and etching treatments [28]. The annealing can be made in the fiber or in the preform [29] and is composed of keeping the fiber in a temperature below the fiber material glass transition temperature (T g ) for some hours [30,31]. In order to increase the strain performance of the POFs, the annealing is made on both non-fused and fused POFs, which were kept in a temperature of 90°C for 24 h. The annealing temperature was chosen considering that the employed POFs present a structure similar to CYTOP fibers, which presents a T g of about 120°C.…”
mentioning
confidence: 99%